Tuning the photoreactivity of Z-hexatriene photoswitches by substituents – a non-adiabatic molecular dynamics study. Issue 38 (19th September 2018) - Tapavicza, Enrico; Thompson, Travis; Redd, Kenneth; Kim, Dan
Abstract : To understand how substituents can be used to increase the quantum yield of electrocyclic ring-closing in Z -hexatriene (HT) photoswitches, we study the photodynamics of substituted HT derivatives using non-adiabatic molecular dynamics. Abstract : To understand how substituents can be used to increase the quantum yield of photochemical electrocyclic ring-closing of the Z -hexa-1, 3, 5-triene (HT) photoswitch forming cyclohexadiene (CHD), we investigate the S1 photo dynamics of HT and its derivatives 2, 5-dimethyl-HT (DMHT), 2-isopropyl-5-methyl-HT (2, 5-IMHT), 1-isopropyl-4-methyl-HT (1, 4-IMHT), and 2, 5-diisopropyl-HT (DIHT) using time-dependent density functional theory surface hopping dynamics. We report detailed photoproduct distributions, formation mechanisms, branching ratios, and wavelength-dependent product quantum yields. Most products have been confirmed experimentally and include all- trans HT derivatives, cyclopropanes, cyclobutenes, cyclopentene, cyclohexadienes, and bicyclic compounds. Regarding CHD formation, we find that for the 2, 5-substituted derivatives DMHT, 2, 5-IMHT, and DIHT, the branching ratios increase with increasing size of the substituents. In contrast the branching ratios of the E / Z -isomerization decrease with increasing size of the substituents. Due to steric interactions, increasing the size of the substituents increases the amount of gZg rotamers in the ground state, which are prone to CHD formation and have lower E / Z -isomerization probability. Furthermore, we find [1, 4], [1, 5], and [1, 6]-sigmatropic hydrogen shift reactions occurring at large percentages (5% to 15%); for sterical reasons these reactions stem from tZg conformers. DIHT shows the lowest percentage of side product formation among the 2, 5-substituted molecules and highest CHD branching ratio; its CHD quantum yield can be increased up to more than 64%, by excitation of DIHT on the red tail of its absorption spectrum, whereas the Z / E -isomerization is reduced below 5% and side reactions practically vanish. This makes DIHT the best candidate for applications in molecular switches.